Perempuan dalam Penanggulangan Bencana: Peran Perempuan dalam Peningkatan Kesiapsiagaan Melalui Table Top Exercise (TTX) - Agus Riyanto; S Supriyati; S Susilastuti; A. Setyabawana Putra (Jagratara: Journal of Disaster Research, 2023)
One of the principles of disaster management in Law Number 24 of 2007 concerning Disaster Management is non-discrimination, towards gender, ethnicity, religion, race and any political sect. This principle applies at every stage of disaster management, both pre-, emergency and post-disaster. In its development, the role of disaster management cannot be generalized to just one group. Gender mainstreaming is one of the strategies adopted so that the principle of non-discrimination can work well. Efforts to apply these principles are carried out in Tabletop Exercise (TTX) preparedness training activities which are carried out for socialization, to provide an understanding of policies, procedures, plans that have been prepared, will be prepared or need to be prepared. It is hoped that the role of women in TTX can provide a more specific perspective regarding the needs and roles that can be filled by women in disaster management. Although the number of female personnel involved in TTX is limited, if they hold key positions they can provide significant results in the implementation of TTX.